Modulatory effects of bioactive natural compounds on pruritic pathways: mechanistic basis and therapeutic prospects - Wagih H. Marcus; Hassan A. Ruby; Amira E. Awwad; Mahrous H. Mahrous; Ebraheem Abouelwafa; Mohamed A. S. Badawy; Riham A. El-Shiekh; Eman S. Zaki; Mahmoud Abdelmouti Mahmoud (Inflammopharmacology, 2025)
Chronic pruritus, characterized by persistent itching, is a significant health issue that adversely affects individuals’ quality of life, particularly in palliative care environments. Conventional treatments frequently do not yield sufficient relief and may lead to undesirable side effects, which has spurred interest in exploring alternative therapeutic options. A thorough literature search was conducted across several databases such as PubMed, Web of Science, Scopus, and EKB, with an emphasis on studies involving in vitro, animal models, and clinical trials utilizing terms like “plant,” “extract,” and “pruritus.” All studies were considered regardless of their publication date and were limited to English-language articles. This review highlights the promise of various medicinal plants, including chamomile, Aloe vera , calendula, curcumin, lavender, licorice, and peppermint, as adjunctive therapies for pruritus. These plants possess a range of pharmacological properties, such as anti-inflammatory, antioxidant, and skin-soothing effects, which are relevant to the complex nature of pruritus. Their favorable safety profiles and natural origins enhance their appeal in holistic and patient-centered care models.